Translation Procedures of the Indonesian Subtitles of English Idiomatic Expressions Found in Inside Out - Jasmine Julie Kusuma; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2020)
This thesis focused on studying the subtitles of idioms found in the movie, Inside Out (2015), specifically the idioms uttered by Joy, Sadness, Anger, Fear, and Disgust. The writer used the following theories by Newmark (2001) to analyze the data—Translation Procedures to sort out the translations, and Translation Criticisms to evaluate the appropriateness of the translations. Through this study, the writer aimed to find the most frequently used translation procedure for idioms in Inside Out, and the appropriateness of its translations. After analyzing the data, the writer concluded Functional Equivalent as the most frequently used translation procedures for idioms found in Inside Out by producing 23 out of 39 translations. Functional Equivalent also produced mainly appropriate translations with 20 translations being appropriate. In conclusion, Functional Equivalent is the most recommended procedure to translate idioms, because it produces referentially and pragmatically accurate, semantically adequate, and natural translations. Key words: Translation, Subtitles, Idioms, Translation Procedures